Subclinical Atherosclerosis, Vascular Risk Factors, and White Matter Alterations in Diffusion Tensor Imaging Findings of Older Adults With Cardiometabolic Diseases - Tamura, Yoshiaki; Shimoji, Keigo; Ishikawa, Joji; Matsuo, Yoshinori; Watanabe, So; Takahashi, Hisae; Zen, Shugo; Tachibana, Aya; Omura, Takuya; Kodera, Remi; Oba, Kazuhito; Toyoshima, Kenji; et al. (Frontiers in Aging Neuroscience, 2021)
White matter abnormalities may reflect cerebral microvessel disease. Diffusion tensor imaging (DTI) can help detect early changes in white matter integrity in each tract. However, studies investigating the relationship between subclinical atherosclerosis markers and white matter alterations in DTI findings are limited. This study aimed to examine associations between cardiovascular risk factors and indices of subclinical atherosclerosis—ankle brachial index (ABI), brachial-ankle pulse wave velocity (baPWV), and carotid artery intima-media thickness (IMT)—and altered white matter integrity in older patients. A total of 224 patients (aged ≥ 65 years) with cardiometabolic disease who underwent magnetic resonance imaging and either plethysmography or cervical ultrasound at the start of the 3-year observational study period were included in this study. We measured fractional anisotropy (FA) and mean diffusivity (MD), which are indices of white matter integrity in seven white matter tracts. In a univariate analysis, lower ABI and higher baPWV values were associated with the loss of white matter integrity in several tracts, whereas IMT was not associated with such loss. In addition, high blood pressure and glycoalbumin/glycohemoglobin ratio (GA/HbA1c) and low body mass index (BMI) and triglyceride (TG) levels were associated with white matter abnormalities. In a multivariate analysis adjusted for age, sex, BMI, diastolic blood pressure, TG, and GA/HbA1c, the associations between ABI and DTI values remained, whereas most of those between baPWV and DTI disappeared. These results indicate that low ABI could be an indicator of white matter abnormalities.